2002
DOI: 10.1046/j.1525-1497.2002.10625.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Mistrust in the Medical Care of Drug Users. The Keys to the "Narc" Cabinet

Abstract: OBJECTIVE: Caring for patients who are active drug users is challenging. To better understand the often difficult relationships between illicit drug–using patients and their physicians, we sought to identify major issues that emerge during their interactions in a teaching hospital. DESIGN: Exploratory qualitative analysis of data from direct observation of patient care interactions and interviews with drug‐using patients and their physicians. SETTING: The inpatient internal medicine service of an urban public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
178
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 42 publications
5
178
0
8
Order By: Relevance
“…Participants also noted the importance of staff who knew how to treat withdrawal, 15 and felt that variation in treatment implied that some providers were delivering substandard care. This mirrors the results of Merrill et al, 16 who found that physicians lacked a standard approach to commonly encountered clinical issues experienced by hospitalized patients with SUD, especially the assessment and treatment of pain and opiate withdrawal. Over a decade later, our findings show a continued need for protocols and staff training to improve provider competence in identifying, assessing, and treating SUD in the hospital.…”
Section: Iscussionsupporting
confidence: 82%
“…Participants also noted the importance of staff who knew how to treat withdrawal, 15 and felt that variation in treatment implied that some providers were delivering substandard care. This mirrors the results of Merrill et al, 16 who found that physicians lacked a standard approach to commonly encountered clinical issues experienced by hospitalized patients with SUD, especially the assessment and treatment of pain and opiate withdrawal. Over a decade later, our findings show a continued need for protocols and staff training to improve provider competence in identifying, assessing, and treating SUD in the hospital.…”
Section: Iscussionsupporting
confidence: 82%
“…How do we ever make a sensible decision? The answer probably lies in the fact that much of what we do is routine, predictable and requires little Obesity [41][42][43][44] Psychiatric illness [45][46][47][48] Age [49][50][51][52] Socioeconomic status 35,53 Sexual orientation [54][55][56] Substance abuse disorders 57,58 Chronic and complex illness 58,59 A 45-year-old woman presents to the emergency department in an agitated state. She is holding a large empty bottle of aspirin and says that she has taken all of the pills a few hours ago to 'end it all'.…”
Section: Discussionmentioning
confidence: 99%
“…det er også vist at smertelindring til opioidavhengige er suboptimal eller ikke-eksisterende (6,9). mangelfulle kunnskaper om hvordan opioidavhengighet påvirker smertebehandling har vist seg å vaere en vesentlig årsak til utilstrekkelig smertelindring (8,10,7). i tillegg til at opioidavhengige pasienter gis utilfredsstillende smertebehandling, blir de også stigmatisert og smertene blir underdiagnostisert (31,12,13).…”
Section: Introduksjonunclassified
“…det kan synes som om helsepersonell er redde for å bli manipulert og lurt. dette gjelder spesielt ved etterspørsel og foreskrivning av opioider (10).…”
Section: Introduksjonunclassified
See 1 more Smart Citation